DNA Bending in the Mycobacterial Plasmid pAL5000 Origin-RepB Complex - Chatterjee, Sujoy (American Society for Microbiology (ASM), 2007)
Plasmid pAL5000 represents a family of relatively newly discovered cryptic plasmids in gram-positive Actinomycetes bacteria. The replication regions of these plasmids comprise a bicistronic operon, repA-repB, encoding two replication proteins. Located upstream is a cis-acting element that functions as the origin of replication. It comprises an ∼200-bp segment spanning two binding sites for the replication protein RepB, a low-affinity (L) site and a high-affinity (H) site separated by an ∼40-bp spacer sequence. The trajectory of the DNA in the RepB-origin complex has been investigated, and it has been found that the origin undergoes significant bending movements upon RepB binding. RepB binding not only led to local bending effects but also caused a long-range polar curvature which affected the DNA sequences 3′ to the H site. These movements appear to be essential for the in-phase alignment of the L and H sites that leads to the formation of a looped structure. A novel property of RepB unearthed in this study is its ability to form multimers. This property may be an important factor that determines the overall trajectory of the DNA in the RepB-origin complex. The results presented in this study suggest that the origins of replication of pAL5000 and related plasmids are highly flexible and that multimeric, RepB-like initiator proteins bind the origin and induce local deformations and long-range curvatures which are probably necessary for the proper functioning of the origin.